Design and development of a stimuli-responsive oral tablet system for the treatment of ulcerative colitis - Bawa, Priya (My University, 2011)
The purpose of this study was to formulate a stimuli-responsive colon-targeted oral tablet (SROT) that was capable of preventing release of the therapeutic agent mesalamine (5-ASA) in the upper gastrointestinal tract (stomach and small intestine) thus ensuring the delivery of a maximal quantity of 5-ASA to the colon. The formulation comprised of 5-ASA-loaded crosslinked chitosan (CHT) granules dispersed within a matrix of pectin, barium chloride (BaCl2), carboxymethylcellulose (CMC) and xanthan gum (XG). The combination of matrix components and granules were compressed into shallow concave tablets and coated with a combination coating solution of pectin and ethylcellulose. Formulation batches were prepared according to the Box-Behnken experimental design and each formulation was evaluated for the in vitro drug release characteristics at various residence times and pH gradients. The mean dissolution time (MDT) in the presence and absence of the colonic enzymes was employed in the determination of the optimized SROT. In vitro drug release studies revealed a distinct responsiveness of the SROT to colonic enzymes with a fractional release of 0.402 in the presence of enzymes vs. 0.152 in the absence of enzymes, after 24 hours. The commercially available comparator product showed irreproducible release profiles over the 24 hour period (SD: 0-0.550) compared to the SROT (SD: 0-0.037). FTIR spectra of the coating showed a disappearance of peaks from 1589-1512cm-1 after exposure to colonic enzymes. In addition, with increasing exposure time to colonic enzymes there was a disappearance of peaks between 1646-1132cm-1 of the tablet indicating polymeric cleavage by colonic enzymes and release of 5-ASA from the tablet. Plasma concentration profiles of the SROT in the pig model produced a Cmax of only 3.77±1.375μg/mL compared to 10.604±2.846μg/mL from the comparator product. Overall, the SROT proved beneficial over the commercially available comparator product due to the mechanism of drug release and responsiveness to colonic enzymes.